Effect of electrical cure of concrete on maturity and compressive strength - Hocaoğlu, İsmail and Uygunoğlu, Tayfun (Revista de la Construcción. Journal of Construction, 2019)
In this study, the effects of concretes which have 250, 300, 350 and 400 kg/m3 cement in per m3 and different voltage level application (0 V, 40 V, 60 V, 80 V and 100 V AC) on concrete maturity have been investigated. It has been researched if there is relationship with maturity and compressive strength on the concrete to which stress intensity has been applied. The electrical current has been applied on fresh concretes for 24 hours whose sizes are 10 × 10 × 35 cm. Their internal temperatures of concretes have been recorded and maturity values have been calculated. It has been concluded that AC stress intensity can be used to accelerate maturity through obtaining optimum degree on concrete’s internal temperature without any compressive strength lost.